Delineation of Banyumas Sub-Basins using Gravity Anomaly Based on Trend Surface Analysis Equation - Hidayat Hidayat; Marjiyono Marjiyono; Zulilmatul S Praromadani; Januar H.Setiawan; G.M. Lucki Junursyah; Subagio Subagio; Ahmad Setiawan; Andrian Ibrahim (Jurnal Geologi dan Sumberdaya Mineral, 2021)
A study using gravity methods in the Banyumas Basin, located in the southern part of Central Java, Indonesia had been conducted to generate a map for regional geological features in sub-volcanic basin related to petroleum system. This study used the first and second-order of Trend Surface Analysis (TSA) to separate gravity anomaly into regional and residual components. Matrix inversion is applied to obtain constants values for both the first and second-order of TSA. To interpret geological features related to oil and gas study, residual components are used for gravity anomaly. Residual anomaly is also compared for both first and second order of TSA with a regional geological map to validate the result. Residual anomaly from the second order of TSA showed a very comparable result to geological features, as shown in the regional geological map, compared to those of the first order of TSA. These results also showed a strong contrast of some important geological features such as the Gabon-Nusakambangan Formation outcrop, Karangbolong outcrop, and the eastern part of the south Serayu mountain arc. This study also displayed two potential subbasins i.e Citanduy and Majenang sub-Basin that might be a possible setting in which source rocks of the Banyumas Basin were deposited. From this study, it can be concluded that TSA showed a reliable result of separating gravity anomaly data set into regional and residual components.Keywords: Gravity anomaly, Banyumas Basin, petroleum system, trend surface analysis (TSA).